1983
DOI: 10.2307/3898480
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Impacts on Northern Great Plains Range Vegetation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, the sensitivity of different habitats to compaction may vary. In a mixed prairie habitat, Payne et al (1983) found that bulk density did not increase when passes with a 4-wheeled vehicle were fewer than 32 times a month between May and September. The discrepancies may be a result of different aspects of the site (e.g., soil type, vegetation, soil moisture, terrain, etc.)…”
Section: Impacts Of Orv Activities On Soil Propertiesmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the sensitivity of different habitats to compaction may vary. In a mixed prairie habitat, Payne et al (1983) found that bulk density did not increase when passes with a 4-wheeled vehicle were fewer than 32 times a month between May and September. The discrepancies may be a result of different aspects of the site (e.g., soil type, vegetation, soil moisture, terrain, etc.)…”
Section: Impacts Of Orv Activities On Soil Propertiesmentioning
confidence: 93%
“…Physical alterations to the soil structure can also result in changes to the hydrology and erosion at the site. Specifically, ORV areas were found to have lower infiltration rates and soil moisture in grassland/shrubland (Wilshire et al, 1978;Eckert et al, 1979;Payne et al, 1983) and desert habitats (Al-Awadhi, 2013). Further, thaw patterns following disturbance with ATVs with different weights and ground pressures were dependent on the seasonal timing and type of the disturbance (Racine and Ahlstrand, 1991).…”
Section: Impacts Of Orv Activities On Soil Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Impact on soldiersí readiness Impact on facilitiesí ability to train Impact on endangered species Impact on critical habitat Payment Payment Payne et al, 1983;Shaw and Diersing, 1990). 20 Knowing that any areas where critical habitat and training lands coincide are at risk, we categorized the levels of risk to critical habitat in the following manner.…”
Section: Camp Pendleton Fort Irwinmentioning
confidence: 99%